Carrier frequency of β-Thalassaemia in Twin-Cities of Islamabad and Rawalpindi - Muhammad Iqbal, Omar Awwab Khan , Abdul Ghani Waseem, Muhammad Tahir (Journal of Rawalpindi Medical College, 2012)
Background: To determine the prevalence of β- thalassaemia carriers in twin-cities of Islamabad and Rawalpindi. Methods: In this descriptive study, people were motivated to get screened for β- thalassaemia trait. Hemoglobin level, RBC count, MCV, MCH was measured. Hemoglobin electrophoresis was performed if MCH was less than 27pg, MCV less than 75fl and RBC count more than 5 million. If HbA2 was 3.5%or higher, thalassaemia trait was diagnosed. Results: A total of 2101 people were screened in camps held at offices of Federal Ministry of Health & Pakistan Post, two villages( Terlai & Phoolgran) in the suburbs of Islamabad, Fatima Jinnah and Foundation Universities and other educational institutions. 85(4.05%) were found to be carriers of β-thalassaemia. Conclusion: β-Thalassaemia Trait has a carrier frequency of around 4% in twin-cities and suburbs